Evaluation of the Use of Propolis and Sodium Hypochlorite as Methods to Control the Contamination of Free-Range Eggs - Giovana Scuissiatto de Souza; Julia Unicki Philipp; Elisana Julek; Gabriela Campi Voltolin; Guilherme Souza Cavalcanti de Albuquerque; Julia Arantes Galvão (Biology and Life Sciences Forum)
There is a high demand for free-range eggs, although these systems may offer a greater microbiological challenge. Therefore, the aim with this study was to evaluate the effectiveness of 30% propolis extract and 1% sodium hypochlorite in reducing the microbiological contamination of free-range eggs. Eighteen eggs were divided into three groups—treated with propolis, hypochlorite and a control—and tested for mesophilic bacterial count. For the eggshells treated by propolis, the average count was 0.6 log CFU·mL−1, for hypochlorite it was 1.3 log CFU·mL−1 and for the control it was 3.26 log CFU·mL−1. It can be concluded that both methods were effective, with propolis being more efficient.